Optical and Morphological Characterizations of Element Oxides Compound (Y2O3 / SeO2) Nano-Composite Structures Synthesized Via Chemistry of Laser Ablation - Ayad F. Al-Kaim (Journal of Global Pharma Technology, 2018)
The elements Oxides compounds S1(Y2O3) & S2(Y2O3/SeO2) are prepared chemically as an initial stage and affected by Laser Neodymium –YAG ablation  energy (200 mJ), pulses (200 pulse) and  frequency (6Hz) at temperature (65°C) with distilled water as a second stage. (XRD) showed that the oxides compounds were Polycrystalline to the two samples with a difference in the intensity values by increasing crystallization in the first sample and the appearance (Y (OH) 3, PLA) of the) Cubic) , (Monoclinic) forms of the yttrium oxide (S1) and in the second sample (S2) confirmed the formation of SeO2 based (Y2O3) in a quadrilateral and Monoclinic. The Field Emission-Scanning Electron Microscopy(FE-SEM)  images of the two samples (Y2O3) & (Y2O3/ SeO2) showed nanoparticles of Yttrium Oxide & Selenium Oxide as multi-shapes (sheets & rods) with (Y2O3: 82nm) and (Y2O3/ SeO2: 91nm) in grain size  showed long nanotubes distributed on the nanoparticles spread more widely (S1), and the sample (2S) showed the presence of selenium as well as SeO2 in varying proportions and in spherical forms spread over the surfaces of the Y2O3 nanoparticles. This was reinforced by the EDX analysis with the presence of these oxides. The results of the optical properties showed the value of absorbance increased in the S2 than in the S1, energy gap for the indirect electronic transmission were observed. They showed that they were semi-conductive materials with values of (3.5 eV) for the first sample & (3eV) in the second sample.Keywords: Laser ablation, Y2O3/SeO2 nanostructure, Optical & structural properties.